PENERAPAN METODE SYSTEMATIC HUMAN ERROR REDUCTION AND PREDICTION APPROACH (SHERPA) UNTUK KESELAMATAN KERJA PADA INDUSTRI PEMBUATAN GARAM DI PT EMPAT SAUDARA - Mewengkang, Ginolha; Punuhsingon, Charles S. C.; Neyland, Johan S. C.; Tamod, Zetly Estefanus (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2024)
EMPAT SAUDARA is a company engagedin manufacturing by producing refined salt. A tany time the production process on the machine certainly haspotential hazards that must be avoided by workers. In addition to the danger sposed by machines, there a real sohazard factors caused by the workers them selves, human error factors or Human Error. This study aimsto